Supernumerary Teeth in Nepalese Children - Singh, Varun Pratap (ScientificWorldJournal, 2014)
Objective. The objectives of the present study were to investigate the prevalence and characteristics of supernumerary teeth in a patient sample of Nepalese children. Study Design. A survey was performed on 2684 patients (1829 females and 1035 males) ranging in age from 6 to 14 for the presence of supernumerary teeth. For each patient with supernumerary teeth the demographic variables (age and sex), number, location, eruption status, and morphology were recorded. Descriptive statistics were performed. Results. Supernumerary teeth were detected in 46 subjects (1.6%), of which 26 were males and 20 were females with a male : female ratio of 1.3 : 1. The most commonly found supernumerary tooth was mesiodens followed by maxillary premolars, maxillary lateral incisor, and mandibular lateral incisor. Of the 55 supernumerary teeth examined, 58.18% (n = 32) had conical morphology, followed by tuberculate (30.90%, n = 17) and supplemental (10.90%, n = 6) forms. The majority of the supernumerary teeth were erupted (56.36%, n = 31). Conclusion. The prevalence of supernumerary teeth in Nepalese children was found to be 1.6%, the most frequent type being mesiodens. Conical morphology was found to be the most common form of supernumerary tooth.